The Boston Tea Party - Burgan, Michael (Minneapolis, MN Compass Point Books, 2001)
Recounts the events leading up to the colonists' defiant act against the British known as the Boston Tea Party, which ultimately climaxed in the American Revolution.
Keywords: Boston Tea Party, 1773.; United States - History - Revolution, 1775-1783 - Causes